2022
DOI: 10.1021/jacs.2c07385
|View full text |Cite
|
Sign up to set email alerts
|

High Electric Field on Water Microdroplets Catalyzes Spontaneous and Ultrafast Oxidative C–H/N–H Cross-Coupling

Abstract: Oxidative C–H/N–H cross-coupling has emerged as an atom-economical method for the construction of C–N bonds. Conventional oxidative C–H/N–H coupling requires at least one of the following: high temperatures, strong oxidizers, transition metal catalysts, organic solvents, light, and electrochemical cells. In this study, by merely spraying the water solutions of the substrates into microdroplets at room temperature, we show a series of oxidative C–H/N–H coupling products that are strikingly produced in a spontan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
85
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 59 publications
7
85
0
1
Order By: Relevance
“…Some argued that H + in water might be eventually reduced to form H 2 by the electrons. 51 However, the comparison of the mass spectra obtained from the experiments conducted in the atmosphere and in N 2 in this study clearly points out that there must be some species in the atmosphere consuming the electrons in microdroplets. To better understand this problem, we monitored the negative-ion mass spectra (Figure 3) when spraying pure water microdroplets both in the atmosphere and in a glove box in which the gaseous contents were carefully controlled.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Some argued that H + in water might be eventually reduced to form H 2 by the electrons. 51 However, the comparison of the mass spectra obtained from the experiments conducted in the atmosphere and in N 2 in this study clearly points out that there must be some species in the atmosphere consuming the electrons in microdroplets. To better understand this problem, we monitored the negative-ion mass spectra (Figure 3) when spraying pure water microdroplets both in the atmosphere and in a glove box in which the gaseous contents were carefully controlled.…”
mentioning
confidence: 66%
“…Increasing the sheath gas pressure also increases the relative intensity of the products because of smaller droplet size. 51 Figure 2 exhibits the mass spectra obtained by spraying Cu II (OX) solutions both in the atmosphere and in a glove box.…”
mentioning
confidence: 99%
“…Researches from our group and others have shown that water microdroplets exhibit unusual reaction properties that are not observed in bulk water or other organic solvents. One possible reason for the unique properties of water microdroplets is the large amount of hydroxyl radicals at the water–gas interface produced by a strong electric field and by contact electrification . Taking advantage of this feature, our group and others have shown that hydrogen peroxide forms in water microdroplets. The hydrogen peroxide originates from the recombination of two hydroxyl radicals at the surface of the water microdroplet.…”
mentioning
confidence: 91%
“…Electric field effects on local chemistry have been seen in a variety of different systems. When electric fields are applied to liquids, an electric double layer (EDL) forms at the liquid interface that screens the interior bulk of the liquid from the electric field. Recently, systems with chemical reactions at the interface, bypassing the normal screening of the electric field by the EDL, have gained interest as they can promote unique new chemistry at the interface. As the chemistry is dependent on the electric field strength, it is of great interest to know the electrostatic potential drop and electric field strength across the interface. Given that EDLs have dimensions that are typically less than the optical diffraction limit, direct measurements of the electric field strength are difficult to obtain.…”
Section: Introductionmentioning
confidence: 99%